Charge-based CMOS digital RF transmitters - Paro Filho, Pedro Emiliano; Craninckx, J.; Wambacq, Piet; Ingels, M. 1967- (Springer, 2016)
This book introduces a completely novel architecture that can relax the trade-off existing today between noise, power and area consumption in a very suitable solution for advanced wireless communication systems. Through the combination of charge-domain operation with incremental signaling, this architecture gives the best of both worlds, providing the reduced area and high portability of digital-intensive architectures with an improved out-of-band noise performance given by intrinsic noise filtering capabilities. Readers will be enabled to design higher performance radio front-ends that consume less power and area, especially with respect to the transmitter and power amplifier designs, considered by many the "battery killers" on most mobile devices. Describes an innovative architecture that has proved to support advanced wireless communication systems, with outstanding noise performance and improved power and area consumption; Provides an in-depth description of underlying concepts, implementation and results achieved; Demonstrates two real implementations, showing design details and measurement results.
Keywords: Radio -- Transmitter-receivers.; Metal oxide semiconductors, Complementary.; Radio frequency integrated circuits.; Power amplifiers.; Low power radio.; Signal integrity (Electronics); elektronické knihy; electronic books